Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.